INTRODUCTION OF THE PEDAGOGICAL SYSTEM OF TACTICAL-STRATEGIC COMPETENCE FORMATION OF FUTURE INFORMATION TECHNOLOGY SPECIALISTS IN THE PRACTICE OF UNIVERSITY EDUCATION - Шаравара, Володимир (SWorldJournal, 2023)
The article considers the process of introducing the pedagogical system of tactical-strategic competence formation of students of the field of knowledge "Information Technologies" in the practice of university education. The content of three stages is giv